The Impact of Using Short Stories to Improve Students' Reading Comprehension in Eleventh Grade of SMA Negeri 2 Palu - Maharani Maharani; Anjar Kusuma Dewi; Maghfira Maghfira; Mocthar Marhum (Journal of Educational Sciences, 2026)
Reading comprehension remains a major challenge in EFL classrooms due to passive teaching methods and low student engagement. This study investigated whether the use of short stories significantly improved the reading comprehension of eleventh-grade students at SMA Negeri 2 Palu. A quasi-experimental design was employed involving two classes: XI E as the experimental group and XI D as the control group. Data were collected through pre- and post-tests. The experimental group showed an increase in the mean score from 83.13 to 92.53, while the control group improved from 74.27 to 81.13. However, the independent t-test indicated that the difference was not statistically significant (t = 0.21, p > 0.05). These findings may be attributed to the relatively short treatment duration and the high initial reading ability of the experimental group, which limited the observable statistical effect. Nevertheless, the N-Gain analysis showed greater learning improvement in the experimental group (0.55) than in the control group (0.27). These findings suggest that short stories have pedagogical potential to support students' reading comprehension despite the absence of statistically significant differences.